Experimental treatment of dysbiosis in colitis with hepatitis - Bocharov, A. V.; Levitsky, A. P.; Badiuk, N. S.; Zukow, W. (Journal of Education, Health and Sport, 2019)
Nonspecific colitis (inflammation of the colon mucosa) is a common gastroenterological disease. The causative factors of this disease are intestinal dysbiosis, which leads to an increase in blood concentration of intestinal endotoxin (lipopolysaccharide), as well as impaired liver antimicrobial function. The purpose of this study was to determine the possibility of preventing colitis, which develops as a result of a combination of dysbiosis and hepatitis, with the help of biotrit, which has an antidysbiotic and hepatoprotective effect. The experiments were conducted on 24 white rats of the Wistar line (males, 1 month old), divided into 3 equal groups: 1 - control (normal); 2 - dysbiosis + hepatitis without treatment; 3 - dysbiosis + hepatitis + drug "Biotrit". Dysbiosis was caused by the antibiotic lincomycin, which was given to rats with drinking water at a dose of 60 mg / kg for the first 5 days. Toxic hepatitis was reproduced in rats using hydrazine hydrochloride. Studies have shown that the phytopreparation Biotrit has a mucosoprotective effect in experimental nonspecific colitis due to both antidysbiotic and antioxidant effects.